English for Specific Purposes Challenges in Speaking for Nursing Students: A Thematic Analysis - Arroyyani, Risa; Setianingsih, Ika Sulis (Universitas Pahlawan Tuanku Tambusai, 2025)
As part of English for Specific Purposes, English for nursing students presents various challenges. The difficulties faced by students can affect their language proficiency. This study aims to investigate the challenges faced by nursing students regarding speaking skills in the context of ESP. By finding out the speaking challenges faced by the students, the teacher can provide appropriate teaching media and method to overcome the challenges. This study employs a qualitative approach with thematic analysis using instruments such as open-ended questionnaires and structured interviews. A total of 46 students participated in this research, with five selected as interview respondents. The results indicate that students face challenges in speaking, including linguistic challenges-such as problems with vocabulary, pronunciation, fluency, and grammar- and psychological challenges including lack of confidence, anxiety, shyness, and fear of making mistakes in front of peers.